Statement of Managerial Education’s Rapid Development Methodology - A. V. Raychenko (Управление)
The methodological basis of scientific research and professional managerial education are the classical and elaborating approaches. Their statement and use are realized in traditional, innovative, and aggregated forms, and it becomes a constructive condition for improving the research and education process in the management area. From this positions justification, statement and application of a rapid development methodology in a process oriented management format are realized. Anticipatory orientation lays a creative potential of thinking, forms an innovative development activity, as well as provides an assimilation and implementation of objective for an urgent result achievement. The rapid development priority provides assimilation of professional knowledge, practical abilities and applied skills of learners with development’s constructive resource, formulation and implementation of impact goals. This methodology becomes a universal basis for assimilation and application of necessary for the practice, innovatively oriented competences of a manager.